Influence of exogenous organic matter on prokaryotic and eukaryotic microbiota in an agricultural soil. A multidisciplinary approach. (March 2015) - Pezzolla, Daniela; Marconi, Gianpiero; Turchetti, Benedetta; Zadra, Claudia; Agnelli, Alberto; Veronesi, Fabio; Onofri, Andrea; Benucci, Gian Maria Niccolò; Buzzini, Pietro; Albertini, Emidio; Gigliotti, Giovanni
Abstract: The effects on bacterial, yeast and fungal communities present within an agricultural soil treated with a pig slurry-derived digestate were studied using a multidisciplinary (biochemical and 454 pyrosequencing platform) approach. Biochemical analyses showed a significant increase of CO2 emissions from soil 5 days after the amendment with digestate, whereas soil microbial biomass (C-biomass) increased significantly only after 12 and 30 days. PLFAs analysis revealed a significant increase in Gram-negative bacteria 90 days after the amendment. Results from 454 pyrosequencing revealed the presence of OTUs attributed to bacteria, yeasts and filamentous fungi. Proteobacteria, Bacteroidetes and Firmicutes exhibited a significant predominance in the first 5 days, whereas Ascomycota became predominant 90 days after the amendment. Overall, both bacterial and yeast + fungal richness exhibited a decreasing trend from 0 to 90 days after the amendment. Canonical analysis of principal coordinates showed that the cumulative effect of amendment and incubation time explained approximately 45% and 36% of the total variance observed in the bacterial and yeast + fungal communities, respectively. The correlation among some bacterial and fungal OTUs suggested the probable existence of specific biological interactions among different phyla. The results reported represent a picture of the changes of soil microbial diversity in relation with some agronomic practices, such as organic amendments. Highlights: An early increase of CO2 emissions were observed after soil amendment. Gram-negative bacteria exhibited a long-term increase after soil amendment. Proteobacteria, Bacteroidetes and Firmicutes predominated in the early stages. Ascomycota became predominant 90 days after amendment. A few relationships between bacterial and fungal OTUs were found.